Global impact of ten-valent and 13-valent pneumococcal conjugate vaccines on invasive pneumococcal disease in all ages (the PSERENADE project): a global surveillance analysis - Bennett, Julia C; Deloria Knoll, Maria; Kagucia, Eunice W; Garcia Quesada, Maria; Zeger, Scott L; Hetrich, Marissa K; Yang, Yangyupei; Herbert, Carly; Ogyu, Anju; Cohen, Adam L; Yildirim, Inci; Winje, Brita A; et al. (The Lancet. Infectious diseases, 2025)
BACKGROUND: Pneumococcal conjugate vaccines (PCVs) that are ten-valent (PCV10) and 13-valent (PCV13) became available in 2010. We evaluated their global impact on invasive pneumococcal disease (IPD) incidence in all ages. METHODS: Serotype-specific IPD cases and population denominators were obtained directly from surveillance sites using PCV10 or PCV13 in their national immunisation programmes and with a primary series uptake of at least 50%. Annual incidence rate ratios (IRRs) were estimated comparing the incidence before any PCV with each year post-PCV10 or post-PCV13 introduction using Bayesian multi-level, mixed-effects Poisson regressions, by site and age group. All site-weighted average IRRs were estimated using linear mixed-effects regression, stratified by product and previous seven-valent PCV (PCV7) effect (none, moderate, or substantial). FINDINGS: Analyses included 32 PCV13 sites (488 758 cases) and 15 PCV10 sites (46 386 cases) in 30 countries, primarily high income (39 sites), using booster dose schedules (41 sites). By 6 years after PCV10 or PCV13 introduction, IPD due to PCV10-type serotypes and PCV10-related serotype 6A declined substantially for both products (age <5 years: 83-99% decline; ≥65 years: 54-96% decline). PCV7-related serotype 19A increases before PCV10 or PCV13 introduction were reversed at PCV13 sites (age <5 years: 61-79% decline relative to before any PCV; age ≥65 years: 7-26% decline) but increased at PCV10 sites (age <5 years: 1·6-2·3-fold; age ≥65 years: 3·6-4·9-fold). Serotype 3 IRRs had no consistent trends for either product or age group. Non-PCV13-type IPD increased similarly for both products (age <5 years: 2·3-3·3-fold; age ≥65 years: 1·7-2·3-fold). Despite different serotype 19A trends, all-serotype IPD declined similarly between products among children younger than 5 years (58-74%); among adults aged 65 years or older, declines were greater at PCV13 (25-29%) than PCV10 (4-14%) sites, but other differences between sites precluded attribution to product. INTERPRETATION: Long-term use of PCV10 or PCV13 reduced IPD substantially in young children and more moderately in older ages. Non-vaccine-type serotypes increased approximately two-fold to three-fold by 6 years after introduction of PCV10 or PCV13. Continuing serotype 19A increases at PCV10 sites and declines at PCV13 sites suggest that PCV13 use would further reduce IPD at PCV10 sites. FUNDING: Bill & Melinda Gates Foundation as part of the WHO Pneumococcal Vaccines Technical Coordination Project.
Keywords: novorozenec; Infant, Newborn; Infant; Humans; Vaccines, Conjugate; pneumokokové infekce; kojenec; lidé středního věku; dítě; Child; Female; Aged; mladý dospělý; dospělí; senioři; lidé; Serogroup; Pneumococcal Infections; séroskupina; pneumokokové vakcíny; předškolní dítě; Adult; ženské pohlaví; Pneumococcal Vaccines; Male; Middle Aged; Adolescent; incidence; Incidence; Aged, 80 and over; Young Adult; senioři nad 80 let; Streptococcus pneumoniae; vakcíny konjugované; Global Health; celosvětové zdraví; mužské pohlaví; Child, Preschool; mladiství